Colistin Resistant A. baumannii: Genomic and Transcriptomic Traits Acquired Under Colistin Therapy - Cafiso, Viviana; Stracquadanio, Stefano; Lo Verde, Flavia; Gabriele, Giacoma; Mezzatesta, Maria Lina; Caio, Carla; Pigola, Giuseppe; Ferro, Alfredo; Stefani, Stefania (Frontiers in Microbiology, 2019)
Even though colistin-based treatment represents the antimicrobial-regimen backbone for the management of multidrug-resistant Gram-negative infections, colistin resistance is still rare, at least as a full resistance, in Acinetobacter baumannii (Ab). We investigated the genomics and transcriptomics of two clinical Extensively Drug Resistance (XDR) colistin-susceptible/resistant (COL-S/R) Ab strain-pairs in which COL-resistance was developed after exposure to colistin therapy. The molecular characterization of the strains showed that all strains belonged to PFGE-A, ST-281, OXA-23 producers, Global Clone-II, and were resistant to imipenem, meropenem, ampicillin/sulbactam, ciprofloxacin, gentamicin, amikacin, trimethoprim/sulfamethoxazole, and susceptible to tigecycline, in agreement with NGS-acquired resistome. COL-R vs. COL-S Ab comparative genomics, mapping on Ab ATCC 17978 and Ab ACICU Reference Genomes, revealed a closely related genomic phylogeny, especially between strain-pair isolates, and distinctive common genomic non-synonymous SNPs (nsSNPs) in COL-R Ab strains. Furthermore, pmrB and pmrC nsSNPs were found. Notably we recovered, for the first time, lpxC and lpxD nsSNPs previously described only in “in-vitro” mutants and associated with colistin resistance in a clinical COL-R Ab. COL-R vs. COL-S Ab comparative transcriptomics evidenced a strain-dependent response to the colistin resistance onset highly variable among the single COL-R strains vs. their COL-S parents and merely seven common over-expressed transcripts, i.e. the PgaB lipoprotein for biofilm-matrix production, the diacylglycerol kinase for the lipid recycling in the membrane-derived oligosaccharide cycle, a membrane non-ribosomal peptide synthetase, the Lipid A phosphoethanol aminotransferase PmrC, and three hypothetical proteins. The transcript analysis of the “COL-R related genes” and the RNA-seq data confirmed pmrCAB over-expression responsible for a greater positive net cell-charge, and lpxACD under-expression in COL-R causing a decreased LPS production, as main mechanisms of colistin resistance. Our study reports the COL-R Ab genomic and transcriptomic signatures reflecting the interplay between several direct and indirect potential adaptations to antimicrobial pressure, including the occurrence of SNP accumulation hotspot loci in genes related to intrinsic or adaptive colistin resistance, surface adhesion proteins and porins, and over-expressed genes involved in different pathways, i.e. biofilm production, oxidative stress response, extensive drug and COL resistance.